Trends in condom use among MSM in the United States: the role of antiretroviral therapy and seroadaptive strategies. (31st July 2016) - Paz-Bailey, Gabriela; Mendoza, Maria C.B.; Finlayson, Teresa; Wejnert, Cyprian; Le, Binh; Rose, Charles; Raymond, Henry Fisher; Prejean, Joseph
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Evaluate changes in condomless anal sex at last sex among men who have sex with men (MSM) and assess if these changes are associated with the adoption of serosorting and biomedical prevention. Design: The National HIV Behavioral Surveillance is a crosssectional survey done in up to 21 cities in 2005, 2008, 2011 and 2014. Methods: MSM were recruited through venue-based sampling. Among men reporting at least one male partner, we evaluated changes in condomless anal sex at last sex with a partner with (1) HIV-concordant (proxy for serosorting) or (2) HIV-discordant (discordant/unknown) status. We hypothesized that if concordant condomless sex was increasing while discordant was stable/declining, the increases could be driven by more men attempting to serosort. We used generalized estimating equations assuming a Poisson distribution and robust variance estimator to explore whether temporal changes in the outcomes varied by selected characteristics. We also assessed changes in condomless anal sex by antiretroviral therapy (ART) use among HIV-positive MSM. Results: Among 5371 HIV-positive MSM, there were increases in concordant (19% in 2005 to 25% in 2014, P  < 0.001) and discordant condomless sex (15 to 19%, P  < 0.001). The increases were not different by ART use. Among 30 547 HIV-negative MSM, concordant (21 to 27%, P  < 0.001) and discordant condomless sex (8 to 13%, P  < 0.001) increased. Conclusion: Our data suggest that condom use decreased among MSM and that the trends are not explained by serosorting or ART. Promotion of condoms and increased access to preexposure prophylaxis are vital to ensure that the benefits of ART in reducing transmission of HIV are not undermined.